2020
DOI: 10.1111/ajt.15889
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cell targeting to prevent antibody-mediated rejection

Abstract: Plasma cells (PCs) are the major source of pathogenic allo-and autoantibodies and have historically demonstrated resistance to therapeutic targeting. However, significant recent clinical progress has been made with the use of second-generation proteasome inhibitors (PIs). PIs provide efficient elimination of plasmablast-mediated humoral responses; however, long-lived bone marrow (BM) resident PCs (LLPCs) demonstrate therapeutic resistance, particularly to first-generation PIs. In addition, durability of antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Rebound of DSA after short-term PI has been reported (136)(137)(138). This repletion of PC and DSA would be partially due to an intra-marrow PC repopulation which might be related to PC populations resistant to PI treatment.…”
Section: Costimulation Blockadementioning
confidence: 86%
“…Rebound of DSA after short-term PI has been reported (136)(137)(138). This repletion of PC and DSA would be partially due to an intra-marrow PC repopulation which might be related to PC populations resistant to PI treatment.…”
Section: Costimulation Blockadementioning
confidence: 86%
“…After immunoglobulin class switching, they undergo affinity maturation and the cells with low affinity for foreign antigens or high affinity for self-antigens undergo apoptosis as a negative selection mechanism, followed by differentiation into MBCs or LLPCs that bind these antigens with high affinity. MBCs migrate to secondary lymphoid tissue to counter the ensuing invasion by foreign antigens, and LLPCs persist and continue to produce antibodies that induce AMR (17,18,(43)(44)(45) (Figure 1).…”
Section: Molecular Pathophysiology In Amrmentioning
confidence: 99%
“…In addition, pathological findings indicate that the CD138-positive PCs infiltrates are associated with AMR development ( 196 ). Therefore, CD138-targeting therapy may be applicable for AMR control and the maintenance of graft function after further elucidation of the involvement mechanism of CD138-mediated signaling in the activation of humoral immunity to transplanted grafts ( 43 ). However, as described in B−cell based therap y , B cells contain a subset that has an immune regulatory function.…”
Section: Development In Amr Controlmentioning
confidence: 99%
“…Therefore, we initiated a desensitization trial with carfilzomib, which is an irreversible proteasome inhibitor. This trial, which is ongoing, has demonstrated increased potency and reduced toxicity compared with bortezomib 111,139,199 . Our group found >65% depletion of bone marrow plasma cells following carfilzomib treatment.…”
Section: Plasma Cell Biologymentioning
confidence: 72%
“…Research over the past several decades has uncovered factors critical for plasma cell survival and has begun to identify potential therapeutic targets to reduce or eliminate plasma cells. Here, we will focus on some of the elements, their respective therapies, and the data on their effectiveness in transplantation which should complement more mechanistic details on plasma cell homeostasis and targeting strategies in transplantation as recently reviewed 109‐115 …”
Section: Plasma Cell Biologymentioning
confidence: 99%